Deskripsi Kreativitas dalam Menyelesaikan Soal Berbasis Timss Ditinjau dari Kemampuan Awal Matematika Siswa SMPN 2 Barombong - Ruslan; Hamda; Nur Rahayu (Issues in Mathematics Education (IMED), 2021)
The research is a qualitative study using a descriptive method that aims to determaine students’ creativity in solving TIMSS-based questions the cognitive domain. The subjects in this study were six students from the VIII C class of SMPN 2 Barombong. The research’s subject is based on the mathematical ability result of the VIII C class. Then, the result is divides students into two categories of mathematical ability: students with high and low abilities. The researcher used the creativity test and interview guidelines to collect the data. The result of this study indicates that (1) the subject in the cognitive domain of applying algebraic content, high initial abilities meet the aspects of fluency and flexibility. Which meant that obtained creative thinking ability level 3 (creative); (2) the subject in the cognitive domain of applying algebraic content, low initial abilities do not meet the aspects of fluency, flexibility, and novelty. Which meant that obtained creative thinking ability level 0 (not creative); (3) the subject n the cognitive domain of reasoning algebraic content that high initial abilities meet the aspect of flexibility. Which meant that obtain creative thinking ability level 2 (creative enough); (4) the subjects in the cognitive domain of reasoning algebraic content that low initial abilities do not meet the aspects of fluency, flexibility, and novelty. Which meant that obtained creative thinking ability level 0 (not creative).